The runner : a novel / by Richard Watson. - Watson, Richard A., 1931- (Copple House Books, 1981)
The story of a man who takes up running in his middle years. Gregory is happily married, the father of twins, an accountant. His inner life is counterpoint to externals--a windjammer cruise in the Caribbean, a climb up the north face of Long's Peak, the gradual estrangement from his wife that begins when she goes to Florida to stay with her aging mother. As these events mark his passage through middle age he becomes increasingly engaged with running to the point where it approaches obsession. Running becomes his chief activity and, finally, a metaphor for his existence.